PENINJAUAN ELECTORAL JUSTICE SEBAGAI UPAYA DALAM MEWUJUDKAN PEMILU 2024 YANG BERKEADILAN (Jurnal Bawaslu Provinsi Kepulauan Riau, 2021)
Indonesia is a constitutional state based on the 1945 Constitution and adopts a democratic form of government. In running with a democratic system governance, each person who is apart of an Indonesian citizenis given the right and authority to choose representatives of the peoplewho will carry out the mandate of the people’s political rights for the sovereignty of the Indonesian citizens.Thus, Indonesia enforcesa general election system to realize a fair democratic process for every Indonesian citizen. However, in the implementation process to embody this goal, there are challenges that must be faced by participants, organizers,nor voters in the election, because disputes and violations are vulnerable to occur both in the election process (such as conflicts that occur between participants), as well as disputes over election results. Therefore, a more in-depth application of justice in elections is needed.Electoral justice is one of the efforts that must be made to uphold democratic events that are in accordance with the main objectives of all Indonesian citizens with an electoral justice system that must be reviewed periodically.